Attitudes, Aptitudes, and Aspirations of American Youth: Implications for Military Recruitment - National Research Council
Recruiting an all-volunteer military is a formidable task. To successfully enlist one eligible recruit, the Army must contact approximately 120 young people. The National Research Council explores the various factors that will determine whether the military can realistically expect to recruit an adequate fighting force2014one that will meet its upcoming needs. It also assesses the military's expected manpower needs and projects the numbers of youth who are likely to be available over the next 20 years to meet these needs. With clearly written text and useful graphics, Attitudes, Aptitudes, and Aspirations of American Youth offers an overview of important issues for military recruiters, touching on a number of important topics including: sex and race, education and aptitude, physical and moral attributes, and military life and working conditions. In addition, the book looks at how a potential recruit would approach the decision to enlist, considering personal, family, and social values, and the options for other employment or college. Building on the need to increase young Americans' \

Offspring: Human Fertility Behavior in Biodemographic Perspective - National Research Council (The National Academies Press, 2003)
Despite recent advances in our understanding of the genetic basis of human behavior, little of this work has penetrated into formal demography. Very few demographers worry about how biological processes might affect voluntary behavior choices that have demographic consequences even though behavioral geneticists have documented genetics effects on variables such as parenting and divorce. Offspring: Human Fertility Behavior in Demographic Perspective brings together leading researchers from a wide variety of disciplines to review the state of research in this emerging field and to identify promising research directions for the future.

Conflict and Reconstruction in Multiethnic Societies: Proceedings of a Russian-American Workshop - National Research Council (The National Academies Press, 2003)
This report is the proceedings of a December 2001 international symposium in Washington, DC organized by the National Academies and the Russian Academy of Sciences. The symposium addressed (1) characteristics of peaceful management of tensions in multiethnic societies, particularly in Russia; (2) policies that have contributed to violence in such societies; (3) steps toward reconciliation; and (4) post-conflict reconstruction.

Guatemala: Human Rights and the Myrna Mack Case - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
Two members of the Committee on Human Rights (CHR), NAS member Mary Jane West-Eberhard and NAS\/NAE member Morton Panish, undertook a mission to Guatemala to observe the trial of two high-level Guatemalan military officials who were charged with ordering the murder of Guatemalan anthropologist Myrna Mack. She was stabbed to death in 1990, two days after a report for which she was principal researcher, \

Owner-Authorized Handguns: A Workshop Summary - National Academy of Engineering (The National Academies Press, 2003)
The feasibility and potential impact of so-called smart handguns has generated considerable public interest and debate. This report summarizes a June 2002 workshop at the National Academy of Engineering that examined three related issues: the state of technology for owner-authorized handguns; the role of product liability in the development and marketing of such firearms; and the potential impact of these smart guns on health and crime. Smart-gun technology has the potential to prevent unintended or undesirable uses of handguns, such as accidental shootings; the shooting of police officers by assailants using the officers' own weapons; suicides; homicides with stolen handguns; and other gun-related crimes. However, information presented at the workshop suggests that considerably more research is needed to bring a reliable and commercially viable product to the marketplace. The report also notes that the impact of smart-guns will be influenced by legal issues, human behavior, economic conditions, and other factors.

Initial Steps in Rebuilding the Health Sector in East Timor - National Research Council (The National Academies Press, 2003)
In May 2002 Timor Leste (East Timor) emerged as a new nation after centuries of foreign rule and decades of struggle for independence. Its birth was a painful one; a United Nations-brokered Popular Consultation in August 1999, in which an overwhelming majority of the people opted for independence, was followed by several weeks of vengeful violence, looting, and destruction by pro-Indonesia militias. It left the territory and all of its essential services devastated. In this context, the United Nations Transitional Administration in East Timor (UNTAET), with the country's leaders and people and many other partners, set about restoring order and services, building a government structure, and preparing for independence. This paper summarizes the rehabilitation and development of the health sector from early 2000 to the end of 2001.

Medicolegal Death Investigation System: Workshop Summary - Institute of Medicine (The National Academies Press, 2003)
The US Department of Justice's National Institute of Justice (NIJ) asked the Institute of Medicine (IOM) of The National Academies to conduct a workshop that would examine the interface of the medicolegal death investigation system and the criminal justice system. NIJ was particularly interested in a workshop in which speakers would highlight not only the status and needs of the medicolegal death investigation system as currently administered by medical examiners and coroners but also its potential to meet emerging issues facing contemporary society in America. Additionally, the workshop was to highlight priority areas for a potential IOM study on this topic.To achieve those goals, IOM constituted the Committee for the Workshop on the Medicolegal Death Investigation System, which developed a workshop that focused on the role of the medical examiner and coroner death investigation system and its promise for improving both the criminal justice system and the public health and health care systems, and their ability to respond to terrorist threats and events. Six panels were formed to highlight different aspects of the medicolegal death investigation system, including ways to improve it and expand it beyond its traditional response and meet growing demands and challenges. This report summarizes the Workshop presentations and discussions that followed them.

International Human Rights Network of Academies and Scholarly Societies: Proceedings - Symposium and Fifth Biennial Meeting, Paris, May 10-11, 2001 (The National Academies Press, 2003)
This report is the proceedings of the fifth biennial meeting of the International Human Rights Network of Academies and Scholarly Societies. (The international Network, created in 1993, consists of 60 national academies and scholarly societies around the world that work to address serious science and human rights issues of mutual concern. The Committee on Human Rights of the U.S. National Academies serves as the Network's secretariat.) The meeting was held on May 10 and 11, 2001, at the Palais de l'Institut de France in Paris. The main events of the meeting were a semipublic symposium, entitled Human Rights and the Scientific Community, and a workshop on a variety of topics related to science, engineering, and health in the human rights context.

Elder Mistreatment: Abuse, Neglect, and Exploitation in an Aging America - National Research Council (The National Academies Press, 2003)
Since the late 1970s when Congressman Claude Pepper held widely publicized hearings on the mistreatment of the elderly, policy makers and practitioners have sought ways to protect older Americans from physical, psychological, and financial abuse. Yet, during the last 20 years fewer than 50 articles have addressed the shameful problem that abusers2014and sometimes the abused themselves2014want to conceal. Elder Mistreatment in an Aging America takes a giant step toward broadening our understanding of the mistreatment of the elderly and recommends specific research and funding strategies that can be used to deepen it. The book includes a discussion of the conceptual, methodological, and logistical issues needed to create a solid research base as well as the ethical concerns that must be considered when working with older subjects. It also looks at problems in determination of a report's reliability and the role of physicians, EMTs, and others who are among the first to recognize situations of mistreatment. Elder Mistreatment in an Aging America will be of interest to anyone concerned about the elderly and ways to intervene when abuse is suspected, including family members, caregivers, and advocates for the elderly. It will also be of interest to researchers, research sponsors, and policy makers who need to know how to advance our knowledge of this problem.

Preparing for the Psychological Consequences of Terrorism: A Public Health Strategy - Institute of Medicine (The National Academies Press, 2003)
The Oklahoma City bombing, intentional crashing of airliners on September 11, 2001, and anthrax attacks in the fall of 2001 have made Americans acutely aware of the impacts of terrorism. These events and continued threats of terrorism have raised questions about the impact on the psychological health of the nation and how well the public health infrastructure is able to meet the psychological needs that will likely result. Preparing for the Psychological Consequences of Terrorism highlights some of the critical issues in responding to the psychological needs that result from terrorism and provides possible options for intervention. The committee offers an example for a public health strategy that may serve as a base from which plans to prevent and respond to the psychological consequences of a variety of terrorism events can be formulated. The report includes recommendations for the training and education of service providers, ensuring appropriate guidelines for the protection of service providers, and developing public health surveillance for preevent, event, and postevent factors related to psychological consequences.

Dynamic Social Network Modeling and Analysis: Workshop Summary and Papers - National Research Council (The National Academies Press, 2003)
In the summer of 2002, the Office of Naval Research asked the Committee on Human Factors to hold a workshop on dynamic social network and analysis. The primary purpose of the workshop was to bring together scientists who represent a diversity of views and approaches to share their insights, commentary, and critiques on the developing body of social network analysis research and application. The secondary purpose was to provide sound models and applications for current problems of national importance, with a particular focus on national security. This workshop is one of several activities undertaken by the National Research Council that bears on the contributions of various scientific disciplines to understanding and defending against terrorism. The presentations were grouped in four sessions 2013 Social Network Theory Perspectives, Dynamic Social Networks, Metrics and Models, and Networked Worlds 2013 each of which concluded with a discussant-led roundtable discussion among the presenters and workshop attendees on the themes and issues raised in the session.

Statistical Issues in Allocating Funds by Formula - National Research Council (The National Academies Press, 2003)
In 2000, the federal government distributed over 260 billion of funding to state and local governments via 180 formula programs. These programs promote a wide spectrum of economic and social objectives, such as improving educational outcomes and increasing accessibility to medical care, and many are designed to compensate for differences in fiscal capacity that affect governments' abilities to address identified needs. Large amounts of state revenues are also distributed through formula allocation programs to counties, cities, and other jurisdictions. Statistical Issues in Allocating Funds by Formula identifies key issues concerning the design and use of these formulas and advances recommendations for improving the process. In addition to the more narrow issues relating to formula design and input data, the book discusses broader issues created by the interaction of the political process and the use of formulas to allocate funds. Statistical Issues in Allocating Funds by Formula is only up-to-date guide for policymakers who design fund allocation programs. Congress members who are crafting legislation for these programs and federal employees who are in charge of distributing the funds will find this book indispensable.

Innovations in Software Engineering for Defense Systems - National Research Council (The National Academies Press, 2003)
Recent rough estimates are that the U.S. Department of Defense (DoD) spends at least 38 billion a year on the research, development, testing, and evaluation of new defense systems; approximately 40 percent of that cost-at least 16 billion-is spent on software development and testing. There is widespread understanding within DoD that the effectiveness of software-intensive defense systems is often hampered by low-quality software as well as increased costs and late delivery of software components. Given the costs involved, even relatively incremental improvements to the software development process for defense systems could represent a large savings in funds. And given the importance of producing defense software that will carry out its intended function, relatively small improvements to the quality of defense software systems would be extremely important to identify. DoD software engineers and test and evaluation officials may not be fully aware of a range of available techniques, because of both the recent development of these techniques and their origination from an orientation somewhat removed from software engineering, i.e., from a statistical perspective. The panel's charge therefore was to convene a workshop to identify statistical software engineering techniques that could have applicability to DoD systems in development.

We're Friends, Right?: Inside Kids' Culture - William A. Corsaro
Sociologists often study exotic cultures by immersing themselves in an environment until they become accepted as insiders. In this fascinating account by acclaimed researcher William A. Corsaro, a scientist \

Deadly Lessons: Understanding Lethal School Violence - National Research Council (The National Academies Press, 2003)
The shooting at Columbine High School riveted national attention on violence in the nation's schools. This dramatic example signaled an implicit and growing fear that these events would continue to occur2014and even escalate in scale and severity. How do we make sense of the tragedy of a school shooting or even draw objective conclusions from these incidents? Deadly Lessons is the outcome of the National Research Council's unique effort to glean lessons from six case studies of lethal student violence. These are powerful stories of parents and teachers and troubled youths, presenting the tragic complexity of the young shooter's social and personal circumstances in rich detail. The cases point to possible causes of violence and suggest where interventions may be most effective. Readers will come away with a better understanding of the potential threat, how violence might be prevented, and how healing might be promoted in affected communities. For each case study, Deadly Lessons relates events leading up to the violence, provides quotes from personal interviews about the incident, and explores the impact on the community. The case studies center on: Two separate incidents in East New York in which three students were killed and a teacher was seriously wounded. A shooting on the south side of Chicago in which one youth was killed and two wounded. A shooting into a prayer group at a Kentucky high school in which three students were killed. The killing of four students and a teacher and the wounding of 10 others at an Arkansas middle school. The shooting of a popular science teacher by a teenager in Edinboro, Pennsylvania. A suspected copycat of Columbine in which six students were wounded in Georgia. For everyone who puzzles over these terrible incidents, Deadly Lessons offers a fresh perspective on the most fundamental of questions: Why?

Survey Automation: Report and Workshop Proceedings - National Research Council (The National Academies Press, 2003)
For over 100 years, the evolution of modern survey methodology2014using the theory of representative sampling to make interferences from a part of the population to the whole2014has been paralleled by a drive toward automation, harnessing technology and computerization to make parts of the survey process easier, faster, and better. The availability of portable computers in the late 1980s ushered in computer-assisted personal interviewing (CAPI), in which interviewers administer a survey instrument to respondents using a computerized version of the questionnaire on a portable laptop computer. Computer assisted interviewing (CAI) methods have proven to be extremely useful and beneficial in survey administration. However, the practical problems encountered in documentation and testing CAI instruments suggest that this is an opportune time to reexamine not only the process of developing CAI instruments but also the future directions of survey automation writ large.